Admission criteria and diversity in medical school. Issue 6 (12th May 2013) - O'Neill, Lotte; Vonsild, Maria C; Wallstedt, Birgitta; Dornan, Tim
<x xml:space="preserve">Abstract</x> Context The under‐representation in medical education of students from lower socio‐economic backgrounds is an important social issue. There is currently little evidence about whether changes in admission strategies might increase the diversity of the medical student population. Denmark introduced an 'attribute‐based' admission track to make it easier for students who may not be eligible for admission on the 'grade‐based' track to be admitted on the basis of attributes other than academic performance. The aim of this research was to examine whether there were significant differences in the social composition of student cohorts admitted via each of the two tracks during the years 2002–2007. Methods This prospective cohort study included 1074 medical students admitted during 2002–2007 to the University of Southern Denmark medical school. Of these, 454 were admitted by grade‐based selection and 620 were selected on attributes other than grades. To explore the social mix of candidates admitted on each of the two tracks, respectively, we obtained information on social indices associated with educational attainment in Denmark (ethnic origin, father's education, mother's education, parenthood, parents living together, parent in receipt of social benefits). Results Selection strategy (grade‐based or attribute‐based) had no statistically significant effect on the social diversity of the medical student population. Conclusions The choice of admission criteria may not be very important to widening access and increasing social diversity in medical schools. Attracting a sufficiently diverse applicant pool may represent a better strategy for increasing diversity in the student population.